FINITE ELEMENT MODEL FOR PREDICTING RESIDUAL STRESSES IN SHIELDED MANUAL METAL ARC WELDING OF MILD STEEL PLATES (Nigerian Journal of Technology, 2015)
This paper investigates the prediction of residual stresses developed in shielded manual metal arc welding of mild steel plates through Finite Element Model simulation and experiments. The existence of residual stresses that cause fatigue and distortion in welded structures has been responsible for failure of machine parts in service. These stresses if not properly controlled can lead to loss of lives and property. The highlight is that various trial and error welding runs have to be carried out while hoping for the best performance during operation. This is wasteful of time, material and finance. Thus the need to incorporate Finite Element Analysis prediction of residual stresses by computational methods to first determine satisfactory welding conditions before actual production. The geometry of the butt welded Low Carbon (ASTM A36) steel plates was modeled and the residual stresses simulated using ANSYS Multiphysics V14. Three experimental samples of similar geometry were also produced using the shielded manual metal arc welding process to verify the result. Low carbon steel (ASTM A36) was used as the parent metal, E066 electrodes were used to complete the weld.  The generated residual stresses were measured using an X-Ray Diffractometer (XRD 6000). From the Finite Element Model Simulation, the transverse residual stress in the x-direction (?x) had a maximum value of 375MPa (tensile) and minimum value of -183MPa (compressive) while in the y-direction (?y), the maximum value of 172MPa (tensile) and minimum value of zero. The longitudinal stress in the x-direction (?x) indicated a maximum value of 355MPa (tensile) and a minimum value of -10MPa (compressive) while in the y-direction (?y), the maximum value was 167MPa and the minimum value of the residual stress was -375MPa. The experimental values as measured by the X-Ray diffractometer were of reasonable correlation as transverse residual stress (?x) along the weld line in the transverse x-direction varied from 353MPa (tensile) to -209MPa (compressive) while in the y-direction, stress (?y) along the weld line varied from 177MPa (tensile) to zero. The longitudinal stress measured by the X-Ray diffractometer in the x-direction (?x) varied from 339MPa (tensile) to zero (compressive) while in the y-direction (?y) varied from 171MPa (tensile) to -366MPa (compressive). These results shows that the residual stresses obtained by prediction from the finite element method are in fair agreement with the experimental results. Based on this, it can be concluded that Finite Element Model can be used to replicate and determine the expected residual stresses that would be generated before an actual welding process is carried out. http://dx.doi.org/10.4314/njt.v35i1.14